(untitled) (Research, Society and Development, 2022)
When applied to the examination of the living, methods for dental age estimation are based on clinical (visual or direct) or radiographic (radiographic or indirect) analyses. Two-dimensional (2D) techniques, such as panoramic radiography, or three-dimensional (3D) imaging modalities, such as cone-beam computed tomography, enable the visualization of multiple anatomical structures simultaneously. The development of each structure contributes to the age estimation process by providing age information. This study tested the performance of age information from rhizogenesis for age estimation. The sample consisted of panoramic radiographs of 568 female (n = 284) and male (n = 284) individuals, aged between 12 and 17.99 years. Tooth development was classified according to Demirjian et al. (1973) technique, and the age was calculated with the method of Willems et al. (2001). The average chronological age of each individual was compared with the estimated dental age, allowing the quantification of the error of the method for each age group at intervals of one year each. For both sexes, there was an overestimation of the chronological age in the age group of 12 |— 14.99 years, while age was underestimated in the age group of 16 |— 17.99 years (p < 0.0001). Statistically significant differences between sexes were observed in the age group of 15 |— 17.99 years (p < 0.05). The increasing error of the method in the late stages of root formation suggests that age information from the scarce remaining apical development of the permanent dentition may not be appropriate enough for sufficiently accurate forensic examinations.